Pengurangan Konsentrasi Amoniak Pada Budidaya Ikan Nila (Oreochromis niloticus) dengan memanfaatkan Karbon Aktif Kulit Pisang Kepok (Musa Acuminate L.) Pada Sistem Resirkulasi - Arfan Affandi; Supasman Emu; Thion Tiffani (AquaMarine (Jurnal FPIK UNIDAYAN ), 2023)
The success of the aquaculture business is closely related to the optimum environmental conditions for the survival and growth of the fish being reared, so it is necessary to improve the aquatic environment. One of the filters that can be used to purify water is by utilizing activated carbon from kapok banana peels. Banana peels contain pectin and cellulose. The purpose of this study was to determine the effect of various uses of activated carbon from kapok banana skin (Musa acuminate L.) with different doses as a filter in a recirculation system on ammonia concentrations in tilapia (Oreochromis niloticus) aquaculture. The fish-rearing containers used were basins with a diameter of 50 cm and a height of 30 cm, totaling 12 pieces, while the filter containers in the form of PVC with a diameter of 3” were 12 pieces. 120 test organisms were used with a size of 5-7 cm. Feeding with a protein content of 25-30% is carried out 2 times a day at 08.00 and 16.00 WITA with a dose of 5% of body weight. This study used a completely randomized design (CRD) with 4 treatments and 3 replications, namely Treatment A (Usual Filtration), Treatment B (Filtration using activated carbon of kapok banana peels as much as 5 g), Treatment C (Filtration using activated carbon of kapok banana peels as much as 10 g) and Treatment D (Filtration using 15g of kapok banana skin activated carbon). The use of activated carbon in kapok banana peels can reduce ammonia levels and increase the survival rate in tilapia cultivation when compared to without the use of activated carbon in kapok banana peels.